First northwestern Pacific records of the deep-sea cardinalfish Epigonus glossodontus (Teleostei, Epigonidae) from the Daito Islands, Japan - Mao Sato; Shohei Ito; Yoshihiro Fujiwara; Keita Koeda (ZooKeys)
The deep-sea cardinalfish Epigonus glossodontus Gon, 1985, previously known only from the Hawaiian Islands, was observed using remotely operated vehicles (ROVs) on steep seafloors surrounding Kitadaito and Minamidaito islands, both being oceanic islands belonging to the Daito Islands, Japan in the northwestern Pacific. A total of 44 hours of ROV observations found sparse populations, each of several individuals, around or within small caves, fissures, and recesses, specifically at depths of 340–588 m within the surveyed depth of 284–1009 m. Seven individuals (36.0–114.8 mm standard length) were successfully collected during the ROV observations around the Daito Islands. A subsequent record of the species (97.5 mm standard length) from the Kyushu-Palau Ridge indicated that the species is widely distributed. A glossy bluish-green body color with black-margined scales was revealed by the field observations, the glossy color fading immediately after death.